Extrato hidroalcoólico de Erithryna mulungu, composições farmacêuticas e processos para produzir essas substâncias - Bolzani, Vanderlan da Silva [UNESP]; Souza, Ricardo Luis Nunes de; Flausino Júnior, Otavio Aparecido (Instituto Nacional de Propriedade Industrial (INPI), 2007)
The present invention provides the use of molecules for cholinergic and/or serotonergic system models, revealing pharmaceutical compositions comprising 11-OH-erythravine, erythravine, erythrartine, pharmaceutically acceptable isotherals, salts, byproducts and/or solvates thereof, optionally containing other erythrina byproducts, for the treatment of anxiety disorders; processes for obtaining said pharmaceutical compositions are also revealed.
Hydroalcoholic extract of erythrina mulungu, pharmaceutical compositios and processes for producing these substances.
Processo: PI0516144-4
Número de publicação: MX2007004690 (A)
Número de aplicação: MX20070004690